Analisis Peran Stakeholders dalam Supply Chain Management - Layla Nurul Sakinah; Putri Salsa Nabila; Siti Aisyah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Stakeholders are people or groups who can influence or be influenced by the goals of the organization. Based on new innovations, initiatives or operational guidelines. Determining the function of stakeholders in supply chain management is the aim of this study. This study employs a qualitative research design using a literature study methodology, which entails a number of tasks like gathering information from the library, reading and taking notes, and processing research materials. Establishing relationships with businesspeople is especially important for individuals who can affect the availability of resources utilized for business operations, such as employees, customers, and owners.